Taʿlīm Qawāʿid al-Lughah al-ʿArabiyyah bi al-Ṭarīqah al-Istiqrāʾiyyah ʿalā Asās al-Muṣṭalaḥāt al-Lughawiyyah al-ʿĀmmah - Edi Cahya Setiadi (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2016)
The teaching of Arabic faces numerous challenges, particularly in translating theoretical concepts into effective classroom practice. These difficulties arise from the complexity of the language's grammatical system, symbols, and linguistic structures. In addition, many students, especially beginners with no prior exposure to Arabic, encounter significant obstacles in understanding the language. In Indonesia, Arabic receives less attention than English because English is generally perceived as offering broader educational and professional opportunities. To address this issue, Arabic teachers are encouraged to adopt engaging instructional approaches that foster students' interest in learning the language. One such approach is integrating Arabic grammar instruction with concepts from general linguistics, particularly through the use of common linguistic terminology familiar in English or Indonesian. This study proposes an inductive approach to teaching Arabic grammar based on general linguistic terminology, providing a practical framework that educators can implement in Arabic language instruction. It is expected that this approach will enable students to develop a more comprehensive and in-depth understanding of Arabic grammar.